COVID‑19 and the Stock Market Crash: Evidence from Indonesia - N. Nurcahyono; D. Purwanto (Финансы: теория и практика)
The purpose of the study is to determine the impact of the COVID‑19 pandemic on the market response, measured by abnormal returns, cumulative abnormal returns and average abnormal returns. The authors use OLS events and regression analysis methods to measure market response at three-time intervals: in the beginning of COVID‑19, during the onset of Delta and Omicron viruses. OLS is used to measure the capital market reaction in the window (–10, +10) for each industry index. The results of the study show that investors reacted very sharply to the onset of COVID‑19, which caused high volatility in the market. Most abnormal returns after the pandemic announcement reacted negatively. Only three sectors — consumer, infrastructure and trade — were in the safe zone. At the same time, the spread periods of Delta and Omicron viruses are characterized by slight differences in the average abnormal yield after the announcement. The results of a study in three time frames concluded that the market response was significant only to five-day (0, +5) ads based on AAR and CAAR.